The Level of Egg Sterility and Mosquitoes Age After The Release of Sterile Insect Technique (SIT) in Ngaliyan Semarang - Sutiningsih, Dwi; Rahayu, Ali; Puspitasari, Devi (Journal of Tropical Life Science, 2017)
Dengue control efforts have not provided adequate results. Therefore we need other measures like sterile in-sect Technique (SIT). This study aimed to observe the level of egg sterility and age of Aedes aegypti mosqui-toes after using SIT in Ngaliyan Semarang. The method of this research is a descriptive study with a cross-sectional design. A sample of the mosquitoes eggs are all the mosquitoes eggs on the paper trap in every house of RW2 population in Ngaliyan village. These samples are the result of the fertilization of male and female mosquitoes in nature. Data analysis using Wilcoxon sign test. The result showed that the average of egg sterility percentage in mosquitoes after using SIT indoors was 73.65% and the average of egg sterility per-centage outdoors was 69.08%. Wilcoxon test showed significant differences in average age of mosquitoes egg (p < 0.05), males pupae (p < 0.05), females pupae (p < 0.05), and adult female mosquitoes (p < 0.05), before and after SIT. It can conclude from this research that the SIT release in Ngaliyan village Semarang city could increase the level of sterility mosquito’s eggs and a decrease of the age of Ae. aegypti mosquitoes in this area.